2016
DOI: 10.1016/j.addbeh.2016.03.027
|View full text |Cite
|
Sign up to set email alerts
|

Impulsiveness, and trait displaced aggression among drug using female sex traders

Abstract: Objective This study compared women who sex trade for drugs, money, or both compared to neither (did not sex trade), and introduced the concept of trait displaced aggression to the literature on sex trading. Methods Female participants (n = 1055) were recruited from a low-income area of southern California. Measures included: the Risk Behavior Assessment (RBA), Barratt Impulsivity Scale (BIS), Eysenck Impulsiveness Scale (EIS), and the Displaced Aggression Questionnaire (DAQ). Results Women who traded sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 51 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Another study showed that aggression and impulsivity were linked with sex exchange for drug use (Clingan et al, 2016). While in Brazilian sample, after analysis multivariate was possible found the relation between lifetime use of crack cocaine with traits of aggression and firearm custody as well more likely to perform unprotected sex the first sex (Narvaez et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Another study showed that aggression and impulsivity were linked with sex exchange for drug use (Clingan et al, 2016). While in Brazilian sample, after analysis multivariate was possible found the relation between lifetime use of crack cocaine with traits of aggression and firearm custody as well more likely to perform unprotected sex the first sex (Narvaez et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, cocaine/crack use was associated with impulsivity and aggression (Comín et al, 2016;Odell et al, 2017). However, the role of the impulsivity and aggressivity in the modulation to exacerbation mental disorders in drug users have been few investigated (Clingan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This study supports other studies of FSWs, which found differences among women based on whether they traded sex for money, drugs, or both. 20,28,29 By categorizing FSWs into those who trade only for money, those who trade only for drugs, those who trade for both money and drugs, and those who do not trade sex, we elaborated upon these findings and found that that those who trade for both drugs and money have a higher overall risk profile than women who trade sex for only money or only drugs. More specifically, FSWs who trade sex for both money and drugs have more sex without using condoms; have a greater number of sex partners and sex partners who inject drugs; self-reported having had most of the STIs that we inquired about; were more likely to test positive on laboratory tests for hepatitis B, hepatitis C, syphilis, and HIV; and had spent substantially more time incarcerated.…”
Section: Discussionmentioning
confidence: 99%
“…19 In a California study, women who traded sex for both drugs and money used more crack cocaine, powder cocaine, and alcohol, whereas those women who only traded sex for drugs used more amphetamine, heroin, and injected drugs more often. 20 The Houston Arrestee Drug Abuse Monitoring Program found that women arrested for prostitution offenses were more likely to test positive for cocaine, and to self-report crack and powder cocaine use, 21 and a New York study found that people who inject drugs who smoked crack or snorted powder cocaine were more likely to exchange sex. 22 More information about the relationship between illicit drug use and form of sex trading can lead to more targeted and cost-effective interventions.…”
Section: Illicit Drug Usementioning
confidence: 99%
See 1 more Smart Citation